Implementasi Metode Simple Additive Weighting pada Sistem Pendukung Keputusan Pemilihan Bibit Cabai Rawit Unggul - Elvis Pawan; Nourman S Irjanto; Ratih Nurul Aprilianti; Syaraswati Syaraswati (Jurnal Bumigora Information Technology (BITe), 2022)
Cayenne pepper is one of Indonesia's mainstay horticultural crops, so the government continues to encourage farmers to maximize chili yields, aiming to achieve chili production targets. In Jayapura City, there are several areas that produce chilies, including in Koya Timur District, where most of the residents are farmers. The problem that occurs in the village of Koya Timur is the frequent crop failures due to pests, bad weather, or improper fertilization, with these problems farmers must be more selective in choosing seeds, so that the cayenne pepper plants that have been planted can survive until harvest. To select chili seeds, DSS was designed using the SAW method. The simple additive weighting (SAW) method is very suitable to be applied in a decision support system for selecting superior chili seeds, because the recommendation or the final result of the SAW method is in the form of rankings so that the selection of alternatives or chili seeds to be planted is very easy. Second, based on the results of testing the system's functionality using the blackbox method, the accuracy and suitability is 100%. Third, based on user acceptance test (UAT) testing, it shows that this system is feasible to implement.